2015
DOI: 10.15407/spqeo18.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescent properties of oxidized stochiometric and carbon-rich amorphous Si1-xCx:H films

Abstract: Abstract. Near-stochiometric and carbon-rich a-Si 1−x C x :H thin films were deposited using the magnetron sputtering of Si target in Ar/CH 4 gas mixture. As-deposited nearstochimetric (x = 0.5) sample showed weak blue photoluminescence (PL), while PL of as-deposited carbon-rich (x = 0.7) sample was 20 times stronger and white in color. The films were annealed in pure argon, wet argon, and dry oxygen at 450 °C for 30 min. The intensity of PL in a-Si 1−x C x :H layers were enhanced by the factor from 2 to 12 af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For example, the hydrogenated amorphous phase of silicon carbide (a-SiC:H) has been demonstrated to be a good candidate for the development of large-area optoelectronic devices due to its light emission and absorption properties. Different methods for obtaining a-SiC:H thin films have been used, such as electron cyclotron resonance (ECR), magnetron sputtering, and Plasma Enhanced Chemical Vapor Deposition (PECVD) [1][2][3];…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the hydrogenated amorphous phase of silicon carbide (a-SiC:H) has been demonstrated to be a good candidate for the development of large-area optoelectronic devices due to its light emission and absorption properties. Different methods for obtaining a-SiC:H thin films have been used, such as electron cyclotron resonance (ECR), magnetron sputtering, and Plasma Enhanced Chemical Vapor Deposition (PECVD) [1][2][3];…”
Section: Introductionmentioning
confidence: 99%
“…These important processes have been used to improve the spectral response, external/internal quantum efficiency, and efficiency of solar cells [4][5][6]. For this purpose, several authors have reported photoluminescence in a-SiC:H. Vasin et al [2] reported the strong PL of a-SiC:H films deposited by sputtering with an annealing process at 450 • C for 30 min in dry oxygen, with values in the range of 1.91-3.26 eV with a peak at 2.66 eV. Li et al [7] obtained luminescence values from 1.75 to 3.1 eV with a peak at 2.48 eV of a-SiC:H using a PECVD system with high power densities (289-520 mW/cm 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation